2014
DOI: 10.1186/1471-2482-14-100
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the preoperative neutrophil-to-lymphocyte ratio in predicting severe cholecystitis: a retrospective cohort study

Abstract: BackgroundTo evaluate whether the neutrophil-to-lymphocyte ratio (NLR), as a prognostic indicator, in patients can differentiate between simple and severe cholecystitis.MethodsA database of 632 patients who underwent cholecystectomy due to cholecystitis during approximately a seven-year span in a single institution was evaluated. Severe cholecystitis was defined when the cholecystitis was complicated by secondary changes, including hemorrhage, gangrene, emphysema, and perforation. The NLR was calculated at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
3
54
0
6
Order By: Relevance
“…[8] NLR is increasingly used to predict the survival of patients with malignancies, coronary artery disease, acute appendicitis, acute cholecystitis, acute pancreatitis, and community-acquired infections. [7] Lee et al [21] found that preoperative NLR accurately predicted the development of severe cholecystitis. Yu et al [22] found that preoperative NLR was prognostic for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8] NLR is increasingly used to predict the survival of patients with malignancies, coronary artery disease, acute appendicitis, acute cholecystitis, acute pancreatitis, and community-acquired infections. [7] Lee et al [21] found that preoperative NLR accurately predicted the development of severe cholecystitis. Yu et al [22] found that preoperative NLR was prognostic for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, total WCC and platelet count have been advocated as indicators of severity of appendicitis, but with varying success [22] . Evidence to date demonstrates that NLR is a good marker of subclinical inflammation, with studies showing that it correlates with the severity of acute inflammatory bowel disease and acute cholecystitis [10,12,13] . Additionally, recent studies have observed that NLR correlates with colorectal cancer stage and oncological outcome and is currently being considered as a biomarker [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, we advocate that these patients should be brought back earlier to the outpatient department for review. Recently, a study examining the role of NLR in forecasting the clinical course of acute cholecystitis found that it had predictive qualities in estimating LOS [10] . Our study also noted that NLR was indicative of total LOS, with severe appendicitis having a median of 1 extra in-patient day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Surgical interventions may be needed to manage diabetic foot infections; these vary from minor to major interventions, such as debridement or amputation. [6,7] The rate of lower extremity amputation (LEA) among patients with diabetes may be as high as 70%, and the most frequent cause of nontraumatic LEA is a diabetic foot ulcer. [810] …”
Section: Introductionmentioning
confidence: 99%